Taking the Internet to the people. - Salvador, T. (IEEE spectrum)
This paper describes how ethnographers from Intel Corp. circled the globe from 2001 to 2005 to determine how computers are being used by typical people in different cultures. The team investigated communities in more than 10 countries in Asia, Europe, Latin America, and North Africa, visiting more than 100 homes and businesses. They observed that at the Internet outposts they visited, even the computer illiterate reap the advantages of the Web. These public Internet facilities are solving real problems, defying cookie-cutter categorizations of nonoriginality, and becoming a growing and vital force in the vast developing world.